مطمٙؿ مٟزع امعمٚمٙمٞم٦ الخم٤صم٦مذ امًم٘م٤مٟقن امًمٚمٞ لٌ مذ مُمٜمٔقرامعذبم٥ احم٤مًمٙلرسالة مقدمة إلى برنامج ماجستير الشريعة بجامعة سوراكارتا المحمدية للحصولعلى درجة الماجستير في الفقه وأصولهHukum Naza' Al-mikiyah Al-khosah Fi Al Qanun Al-lia FI Mandzur Al-Madzatb Al-malil - Kabir, Maryam Adel Salem; , Dr. Muchammad Ichsan, Lc., MA; , Dr. M. Abdul Kholiq Hasan, M.A., M.Ed (2014)
The rule of expropriate private property in Libyan law. From the perspective of the Maliki school .Master Thesis provided to get Master of law degree at the University of Muhammadiyah, Surakarta . Written by: Maryam Adel Salem Kabir. Student's numper: O200130006. The supervisors: Dr. muhammed abdul alkhaleq hassan and Dr. Muhammed ehsan. 2014/1435H. This master's thesis is a library research Its idea based on the need of Libyan street to know and clarify The provisions of the property expropriation Based on the opinions of the Maliki school Research problems statement focused on the study of the opinions of Malki school about the law No (4) for the year 1978 (the Expropriation of property in Libyan law). And after going deep in research and study In the words and opinions of scholars , scientists and the Contemporary of Maliki school and also study and analyzing the law No (4) and its Executive Regulations. The researcher concluded that: Expropriation law in Libya which known as law no (4) And its implementing regulations does not apply with any base or Jurisprudential opinion. And its became unjustly by the Libyan state in the right of its citizens, The occurrence of the sinfulness of people who have benefited from this law and Libyan government should redress who are affected by this law.